20th-century Music in Sweden. An Overview - Martin Knust (Muzikološki Zbornik, 2018)
Sweden appeared as a music exporting country on the map in the beginning of the 20th century. Located between different shifting military and political blocks it maintained a politics that contributed to some extent to the specific shape of Sweden’s music life which this overview outlines.